Diagnostic complexity in the older patient: an unusual presentation of advanced biliary disease. (18th June 2021) - Hosty, Jennifer; Narramore, Ruth; Boothroyd, Matthew; Ramanath, Rekha
Abstract: Biliary disease is common in the older population, and gallbladder dysfunction and increased bile lithogenicity predispose to calculi formation. This case demonstrates an unusual presentation of gallbladder empyema. A 90-year-old male with metastatic prostate cancer presented with hypoactive delirium. With no localising features, normal liver function tests but persistently raised inflammatory markers, he was initially managed as a urinary tract infection. Chest wall discomfort and swelling over the right costal margin later developed. Abdominal imaging demonstrated a massive gallbladder empyema invaginating through the lower right rib cage, causing the superficial swelling. Pre-morbid status prevented cholecystectomy and he was managed conservatively with percutaneous cholecystostomy and antibiotics. He was discharged to 24-h care 2 weeks after diagnosis with a long-term drain.